2016
DOI: 10.1074/jbc.m115.700534
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Amino Acid Transporter ASCT2 (SLC1A5) Reveals an Essential Role for Transporters SNAT1 (SLC38A1) and SNAT2 (SLC38A2) to Sustain Glutaminolysis in Cancer Cells

Abstract: Many cancer cells depend on glutamine as they use the glutaminolysis pathway to generate building blocks and energy for anabolic purposes. As a result, glutamine transporters are essential for cancer growth and are potential targets for cancer chemotherapy with ASCT2 (SLC1A5) being investigated most intensively. Here we show that HeLa epithelial cervical cancer cells and 143B osteosarcoma cells express a set of glutamine transporters including SNAT1 (SLC38A1), SNAT2 (SLC38A2), SNAT4 (SLC38A4), LAT1 (SLC7A5), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
246
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(264 citation statements)
references
References 51 publications
(47 reference statements)
17
246
1
Order By: Relevance
“…To address this question a HeLa SNX27 KO cell line (18) were examined. We initially examined any changes of ASCT2 along with SNAT1 (SLC38A1) and SNAT2 (SLC38A2), the two other amino acid transporters implicated in cellular glutamine uptake (19), at the transcriptional level. Quantitative real time PCR analysis by TaqMAN assay demonstrated that the KO of SNX27 did not affect the gene expressions levels of these transporters ( Fig.2A).…”
Section: Snx27 Interacts With Asct2 Cytoplasmic Pdzbmmentioning
confidence: 99%
“…To address this question a HeLa SNX27 KO cell line (18) were examined. We initially examined any changes of ASCT2 along with SNAT1 (SLC38A1) and SNAT2 (SLC38A2), the two other amino acid transporters implicated in cellular glutamine uptake (19), at the transcriptional level. Quantitative real time PCR analysis by TaqMAN assay demonstrated that the KO of SNX27 did not affect the gene expressions levels of these transporters ( Fig.2A).…”
Section: Snx27 Interacts With Asct2 Cytoplasmic Pdzbmmentioning
confidence: 99%
“…To this end, glutamine uptake was measured in the presence and absence of Na + , and compared to the same transport activities in the presence of inhibitor. In Figure 5B the inhibition of net Na + -dependent glutamine transport is shown, which is largely mediated by ASCT2 (Broer et al, 2016). Leucine transport in MCF-7 cells, by contrast, is largely mediated by system L (molecular isoforms LAT1 or LAT2), which can be inhibited by the amino acid analogue 2-aminobicyclo[2.2.1]heptane-2-carboxylic acid (BCH, Figure 5C) and α-methyl-tyrosine.…”
Section: Figurementioning
confidence: 99%
“…Unfortunately, both compounds are less than optimal. Although employed to suppress ASCT2 activity, benzylserine has been recently found ineffective in inhibiting the transporter in Xenopus oocytes [9], while it directly inhibits LAT1 in the same model [10]. Conversely, in the same model, GPNA exhibited a marked inhibitory effect on ASCT2, but the inhibitor also suppressed the activity of several SNAT transporters [9].…”
Section: Gln Transport As a Therapeutic Target: Problems And Limitationsmentioning
confidence: 99%
“…Although employed to suppress ASCT2 activity, benzylserine has been recently found ineffective in inhibiting the transporter in Xenopus oocytes [9], while it directly inhibits LAT1 in the same model [10]. Conversely, in the same model, GPNA exhibited a marked inhibitory effect on ASCT2, but the inhibitor also suppressed the activity of several SNAT transporters [9]. In spite of lack of a complete structural characterization of the carrier, other ASCT2 inhibitors have been proposed and used in experimental therapy [11], but their specificity awaits confirmation.…”
Section: Gln Transport As a Therapeutic Target: Problems And Limitationsmentioning
confidence: 99%
See 1 more Smart Citation